SAT0357 As Compared with Allopurinol Only Febuxostat Preserves Vascular Function in Patients with Chronic Tophaceous Gout. (23rd January 2014) - Tausche, A.-K.; Christoph, M.; Forkmann, M.; Richter, U.; Aringer, M.; Wunderlich, C.
Abstract : Background: Gout patients often suffer from metabolic comorbidities, such as arterial hypertension, hyperlipoproteinaemia, or diabetes which, presumably via deteriorating endothelial function, frequently result in increased vascular stiffness. Increased arterial stiffness has been shown to contribute to cardiovascular morbidity and mortality. Aortic pulse wave velocity (PWV) is a reliable indicator of arterial stiffness with prognostic value for cardiovascular events. Objectives: We aimed to prospectively evaluate whether an effective 12-month uric acid lowering therapy with the available xanthinoxidase-inhibitors allopurinol and febuxostat in patients with chronic tophaceous gout has an impact on vascular function. Methods: Into our prospective investigation only patients with chronic tophaceous gout who did not receive active uric acid lowering therapy were included. Initially, a thorough clinical evaluation, quantification of serum uric acid levels (SUA) and assessment of vascular functions by carotid to femoral pulse wave velocity (cfPWV) measurement were performed. Subsequently, as per discretion of the treating physician, the participants were either treated with allopurinol (9 patients, doses ranging between 300-600 mg daily) or with febuxostat (8 patients, doses between 80-120 mg daily) to target a SUA level below 360 µmol/L. The co-medication was not changed during this period. After 1 year of active treatment with either allopurinol or febuxostat both the SUA levels and the cfPWV were measured again. Results: The baseline characteristics of both patient groups showed no differences in their gout characteristics or initial level of SUA. Except moderate impairment of renal function (eGFR<60 ml/min) which was more often seen in the febuxostat group (5/8 vs. 0/9 in the allopurinol group) other comorbidities showed no differences. Likewise, the groups did not differ in their baseline cfPWV (allopurinol group: 14.1±3.4 m/s, febuxostat group: 13.7±2.7 m/s, p=0.80). After the treatment period, however, we observed a significant cfPWV increase (to 16.8±4.3 m/s, p=0.001) in the allopurinol group whereas cfPWV in the febuxostat group remained almost stable (13.3±2.3 m/s, p=0.55). It is interesting that this discordant effect on vascular function was observed, while uric acid lowering therapy with either inhibitor of xanthinoxidase resulted in almost equally effective reduction of SUA levels (allopurinol group: baseline 488±120 µmol/L to 298±47 µmol/L after 12 months, p=0.004; febuxostat group: baseline 481±84 µmol/L to 287±98 µmol/L after 12 months, p=0.001). Almost all patients (9/9 and 7/8 patients) reached SUA levels below 360 µmol/L (in the allopurinol and febuxostat groups, respectively). Conclusions: Both febuxostat and higher-doses of allopurinol effectively lower SUA levels in patients with severe gout. However, febuxostat also appeared to prevent further arterial stiffening in these patients, which was observed with allopurinol treatment. Since cardiovascular events are an important issue in treating patients with gout, this unexpected finding may have important implications. Disclosure of Interest: None Declared